Vascular photobiomodulation increases muscle fiber diameter and improves the gait during compensatory hypertrophy of plantar muscle in rats - Martinelli, Andréia; Andreo, Lucas; Santos Malavazzi, Tainá Caroline; Terena, Stella Maris Lins; Cruz Tobelem, Daysi; Bussadori, Sandra Kalil; Fernandes, Kristianne Porta Santos; Mesquita‐Ferrari, Raquel Agnelli (Journal of biophotonics, 2022)
The local photobiomodulation (LPBM) has demonstrated positive effects during compensatory hypertrophy (CH) in skeletal muscle as a response to an overload. The aim was to compare the effects of the transcutaneous vascular photobiomodulation (VPBM) and the LPBM on muscle fiber size, gait functionality, and on mechanical sensitivity during the CH model in rats. VPBM was administered over the rat's main tail vein and LPBM was applied over the plantar muscle region. VPBM induced an increase in muscle fiber diameter and cross‐sectional area (CSA) after 7 days. At 14 days, an increase in the fiber diameter was found in both irradiated groups. The VPBM and LPBM promoted the reestablishment of normal gait evaluated by the sciatic functional index after 14 days. No changes were found in the mechanical (nociceptive) sensitivity in VPBM and LPBM groups in comparison to the CH group but there was an increase in the nociceptive sensitivity in the CH groups in comparison to the control after 7 and 14 days. In conclusion, both PBM, vascular and local, were able to improve the muscle size and gait during the CH process with more pronounced effects when irradiation was performed systemically (VPBM). Experimental procedure: compensatory hypertrophy induction and the modality of PBM (LPBM and VPBM) used.